2018
DOI: 10.1111/ijpo.12270
|View full text |Cite
|
Sign up to set email alerts
|

Circannual variation in relative weight of children 5 to 16 years of age

Abstract: The monthly pattern does not fully agree with previous two-point school-based studies. Results raise concern that the use of two time point measures of BMIs (early fall and late spring) is suboptimal for evaluation of circannual variation. We suggest that future evaluation of the effect of school-based or summer interventions utilizes additional measures in those periods so that a seasonal analysis can be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…This pattern was not readily apparent in prior studies where few BMI measures were available . It differed somewhat from recent studies in southern Wisconsin and Denmark, where BMI increases appeared flatter or nearer to linear during the school months. We also observed an unexpected mid‐winter nadir in BMI z‐scores.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…This pattern was not readily apparent in prior studies where few BMI measures were available . It differed somewhat from recent studies in southern Wisconsin and Denmark, where BMI increases appeared flatter or nearer to linear during the school months. We also observed an unexpected mid‐winter nadir in BMI z‐scores.…”
Section: Discussioncontrasting
confidence: 92%
“…Consistent with prior studies, 14,15,29 kids who were non-White or Hispanic were clearly larger for their age relative to kids who were non-Hispanic White. And by adolescence, BMI z-scores were markedly larger throughout the year for all kids, which is consistent with the higher rates of overweight and obesity observed in older (childhood) age groups across the United States.…”
Section: North-central Wisconsin Children and Adolescents Did Not Shosupporting
confidence: 87%
See 2 more Smart Citations
“…Most of these studies, however, included only two yearly measurements of BMI limiting the ability to examine the effect of season versus school year or school holiday environments on weight gain velocity. The limitations of biannual measurements were highlighted by a cross‐sectional examination of monthly differences in close to 70,000 children's standardized BMI (BMIz) . When researchers simulated what their results would have been if they had only used biannual measurements as was done in the studies based on the academic school year, they found similar patterns of improvements in BMIz during the school year and increases during the summer.…”
Section: Circannual Rhythms and Their Entrainmentmentioning
confidence: 99%